2015
DOI: 10.1371/journal.pone.0135703
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Bordetella bronchiseptica Isolates from Swine and Companion Animals and Detection of Resistance Genes

Abstract: Bordetella bronchiseptica causes infections of the respiratory tract in swine and other mammals and is a precursor for secondary infections with Pasteurella multocida. Treatment of B. bronchiseptica infections is conducted primarily with antimicrobial agents. Therefore it is essential to get an overview of the susceptibility status of these bacteria. The aim of this study was to comparatively analyse broth microdilution susceptibility testing according to CLSI recommendations with an incubation time of 16 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 61 publications
6
23
0
Order By: Relevance
“…In another study on companion animal isolates including dogs and cats (Prüller et al . ), similar MIC 50/90 values were observed with the exception of lower MIC 50/90 for trimethoprim/sulfamethoxazole (0·06/2 μ g ml −1 ) and lower MIC 90 for doxycycline and tetracycline (0·25–0·5 μ g ml −1 ). However, two other studies on isolates almost entirely obtained from dogs and cats reported similar enrofloxacin MIC 90 values as our work (Speakman et al .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In another study on companion animal isolates including dogs and cats (Prüller et al . ), similar MIC 50/90 values were observed with the exception of lower MIC 50/90 for trimethoprim/sulfamethoxazole (0·06/2 μ g ml −1 ) and lower MIC 90 for doxycycline and tetracycline (0·25–0·5 μ g ml −1 ). However, two other studies on isolates almost entirely obtained from dogs and cats reported similar enrofloxacin MIC 90 values as our work (Speakman et al .…”
Section: Discussionsupporting
confidence: 71%
“…Prüller et al . ). Despite their importance, standardized, ongoing RTI surveys are uncommon and, hence, only limited information is available about antimicrobial susceptibility of RTI pathogens of dogs and cats.…”
Section: Introductionmentioning
confidence: 97%
“…B. bronchiseptica bacteriophage examination, however, is important from several aspects. For many multiple resistant bacteria, bacteriophages can be an alternative to conventional antibiotics [14], and B. bronchiseptica possesses innate or acquired antibiotic resistance to β-lactams, macrolides, tetracyclines, sulphonamides, and aminoglycosides, usually used for the treatment of animals with respiratory infections [15]. Furthermore, phage genomes can be new sources of genes for lytic enzymes, i.e., enzybiotics, as well as other valuable proteins [16].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial susceptibility profiles have recently been published for B. bronchiseptica isolates from swine and companion animals [36]. B. bronchiseptica is generally resistant to macrolide antibiotics and cephalosporins and often carries b-lactamase resistance genes.…”
Section: Prevention and Controlmentioning
confidence: 99%